The Juno Mission 2014
DOI: 10.1007/978-94-024-1560-5_8
|View full text |Cite
|
Sign up to set email alerts
|

The Ultraviolet Spectrograph on NASA’s Juno Mission

Abstract: The ultraviolet spectrograph instrument on the Juno mission (Juno-UVS) is a long-slit imaging spectrograph designed to observe and characterize Jupiter's far-ultraviolet (FUV) auroral emissions. These observations will be coordinated and correlated with those from Juno's other remote sensing instruments and used to place in situ measurements made by Juno's particles and fields instruments into a global context, relating the local data with events occurring in more distant regions of Jupiter's magnetosphere. Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 51 publications
2
67
0
Order By: Relevance
“…Figure focuses on the PJ8 observations and the relationship with possible auroral injection signatures measured by the ultraviolet spectrometer (UVS) instrument on Juno (Gladstone et al, ). Here in addition to the proton spectrogram (same as in Figure b) we include electron spectrograms showing injections (Figure b) with an inverted energy scale.…”
Section: Jedi Observationssupporting
confidence: 55%
“…Figure focuses on the PJ8 observations and the relationship with possible auroral injection signatures measured by the ultraviolet spectrometer (UVS) instrument on Juno (Gladstone et al, ). Here in addition to the proton spectrogram (same as in Figure b) we include electron spectrograms showing injections (Figure b) with an inverted energy scale.…”
Section: Jedi Observationssupporting
confidence: 55%
“…Observations made by the Hubble Space Telescope were interpreted using color ratio, which allowed incident electron energies to be estimated (Gérard et al, ). This has been followed by color ratio measurements made by the UV spectrometer on board the Juno spacecraft (Bonfond et al, ; Connerney et al, ; Gladstone et al, ). Both Gérard et al () and Bonfond et al () have shown color ratios between 1 and 20 for the Juno UV observations.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, infrared observations of Jupiter aurorae, more than being an instantaneous picture of the particle precipitation process as they are in the UV, also monitor the H 3 + column density and temperature. Together with JIRAM, Juno mission carries an UV auroral spectrograph (UVS, Ultraviolet Spectrograph [ Gladstone et al ., ]), to allow comparison of simultaneous observations of both IR and UV emissions from the same regions. JIRAM‐UVS comparison, to be performed in future studies, will give more insights on the auroral processes, allowing studies that are not possible by analyzing IR or UV data alone.…”
Section: Introductionmentioning
confidence: 99%